2020
DOI: 10.1002/ptr.6584
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinic acid reverses non‐small cell lung cancer cisplatin resistance by activating the MAPK signaling pathway

Abstract: Cisplatin (DDP) is one of the first-line chemotherapeutic agents for non-small cell lung cancer (NSCLC). However, repeated use of cisplatin in clinical practice often induces chemoresistance. The aims of this study were to investigate whether rosmarinic acid (RA) could reverse multidrug resistance (MDR) in NSCLC and to explore the underlying mechanisms. Our data demonstrated that RA significantly inhibited NSCLC cell proliferation and cell colony formation in a dose-dependent manner, induced G1 phase cell cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 43 publications
1
36
0
Order By: Relevance
“…mTOR inhibitor (CCI-779) appears to reverse DDP resistance by increasing the growth inhibition and enhancing the apoptotic effect in DDP resistant cells (29). Rosmarinic acid reverses NSCLC resistant to DDP by activating the MAPK signaling pathway (21). Our results indicated that AMPK and AKT signaling pathways involved in NSCLC cells resistant to DDP by GO and KEGG analysis, which provided potential targets for overcoming DDP resistance.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…mTOR inhibitor (CCI-779) appears to reverse DDP resistance by increasing the growth inhibition and enhancing the apoptotic effect in DDP resistant cells (29). Rosmarinic acid reverses NSCLC resistant to DDP by activating the MAPK signaling pathway (21). Our results indicated that AMPK and AKT signaling pathways involved in NSCLC cells resistant to DDP by GO and KEGG analysis, which provided potential targets for overcoming DDP resistance.…”
Section: Discussionmentioning
confidence: 66%
“…Previously we established A549DDP cell line with persistent DDP resistance and the resistance index (RI) value was 11.19 ± 0.50 (21). To investigate the effect of Cor on NSCLC cells, we treated A549 and A549DDP cells with various concentrations of cordycepin for 48 hr and measured cell viability by CCK-8 assay.…”
Section: Cor Reverses Cisplatin Resistance In Nsclc Cellsmentioning
confidence: 99%
“…We have established the A549DDP cell line with persistent DDP resistance and the resistance index (RI) was 11.19 ± 0.50 ( Liao et al, 2020 ). To investigate the effect of Cor on NSCLC cells, we treated A549 and A549DDP cells with various concentrations of Cor for 48 h and measured cell viability by CCK-8 assay.…”
Section: Resultsmentioning
confidence: 99%
“…mTOR inhibitor (CCI-779) appears to reverse DDP resistance by increasing the growth inhibition and enhancing the apoptotic effect in DDP-resistant cells ( Wu et al, 2005 ). Rosmarinic acid reverses NSCLC resistant to DDP by activating the MAPK signaling pathway ( Liao et al, 2020 ). Our results of GO and KEGG analysis indicated that AMPK and AKT signaling pathways are involved in NSCLC cells resistant to DDP, which provided potential targets for overcoming DDP resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Plant derived-natural compounds are able to target molecular signaling pathways involved in cancer growth and metastasis (Zhang et al, 2019;Liao et al, 2020). Accumulating data exhibit that the PI3K/Akt signaling pathway plays a significant role in cancer growth and metastasis.…”
Section: Apigenin and Cancer Metastasismentioning
confidence: 99%